Studying the effect of using A1₂O₃/H₂O nanofluid with a polymeric nature in the performance of heat exchanger: دراسة تأثير استخدام مائع نانومتري A1₂O₃/H₂O ذو طبيعة بوليميرية في أداء المبادل الحراري - Tammam Mohammad Alhaddo, Bassam Alkairawan, Ibrahim Alghoraibi (Journal of engineering sciences and information technology, 2022)
In this experimental study, A1₂O₃ nanoparticles with an average diameter of 50nm were used to prepare three volume concentrationfrom Heat transfer nanofluid A1₂O₃/H₂O by two step method. The dimensions of A1₂O₃ were described by Atomic Force Microscopy (AFM). The stability of the nanoparticles is evaluated by Zeta potential and transmission electron microscopy (TEM). Polyacrylamide (PAAM) was used as a material to help disperse and stabilize nanoparticles. The thermal conductivity of nanofluid was measured by a device which works by the hot wire method. The results showed an increase in the thermal conductivity with increasing concentration of nanoparticles, where the improvement percentage was 5.3% at 0.25% vol and 60°C compared with the base liquid. The nanofluid tested as a hot liquid in Double- pipe heat exchanger, The results showed an improvement in the thermal indicators of the exchanger, such as the efficiency, the total heat transfer coefficient, the amount of heat exchanged, and heat transfer units. The heat exchanger showed high efficiency with an increase in the concentration of nanoparticles and the pumping capacity, as the highest value of the total performance coefficient reached 1.186, despite the increase in the friction factor with the increase in the concentration of A1₂O₃ nanoparticles.